2017
DOI: 10.1590/1980-5373-mr-2017-0637
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Ti-12Mo-8Nb Alloy Hot Swaged and Treated for Orthopedic Applications

Abstract: Metastable β-type Ti alloys with non-toxic addition elements such as Mo, Zr, Sn, Ta and Nb were developed as an alternative to the widely used Ti-6Al-4V alloy for biomedical applications. These alloys possess enhanced biocompatibility and reduced elastic modulus in comparison with Ti-6Al-4V. Moreover, for orthopedic implants, low Young's modulus is required in order to avoid the stress shielding phenomenon. This study analyzes the microstructure and mechanical properties of a new Ti-12Mo-8Nb alloy after hot sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 34 publications
0
8
0
1
Order By: Relevance
“…Dercza et al 29 obtained a Young's modulus value of 67 GPa for the single β phase in the Ti-70Ta alloy (Mo eq. =15.4wt.%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dercza et al 29 obtained a Young's modulus value of 67 GPa for the single β phase in the Ti-70Ta alloy (Mo eq. =15.4wt.%).…”
Section: Resultsmentioning
confidence: 99%
“…Due to this characteristic its necessary to find the best relation between these two properties. For this reason, the hardness/ modulus ratio is often used to evaluate the mechanical performance of metallic biomaterials for implants 29 .…”
Section: Resultsmentioning
confidence: 99%
“…This elastic modulus value is substantially lower than the elastic moduli of Ti-Mo-Nb alloys reported in the literature. [17][18][19] Furthermore, Ti-11.1Mo-10.8Nb alloy possessed both lower elastic modulus and higher yield strength, which are also desirable for orthopaedic applications because of the large elastic recovery strain.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Also, Karthega et al 16 , Oliveira et al 17 , and Zhou et al 18 showed that Ti-Mo alloys have excellent corrosion resistance against simulated body fluids 13 . Other studies have shown that Ti-Mo-Nb alloys presented good mechanical properties, corrosion resistance 19 – 21 , and adequate in-vitro biocompatibility 22 . Mo is also a strongly β-stabilizing element.…”
Section: Introductionmentioning
confidence: 98%